Spicing the Subaltern: Food, Gender, and Resistance in Chitra Banerjee Divakaruni’s The Mistress of Spices (International Journal of Food and Nutritional Sciences, 2022)
Chitra Banerjee Divakaruni’s The Mistress of Spices (1997) offers a nuanced narrative framework for examining the intersections of food, identity, and subalternity within the diasporic Indian context. This paper explores how the novel utilises the language of food, particularly the symbolism of spices, to construct a gastrosubaltern consciousness in which culinary practice serves both as a means of empowerment and as a tool of regulation. Through the character of Tilo, the narrative reimagines the spice shop as a liminal space that mediates between cultural memory and assimilation, tradition and modernity, and silence and speech. This paper argues that Divakaruni transforms spices from mere culinary ingredients into epistemological and political instruments that express the silenced experiences of migrant women. By navigating the boundaries between gendered servitude and spiritual mastery, Tilo’s relationship with food challenges patriarchal and colonial narratives that dictate dietary practices. The novel’s examination of the politics of purity, healing, and desire further illustrates how food mediates caste, class, and religious hierarchies, thereby extending the discourse of gastrosubalternism into transnational contexts.Drawing on postcolonial feminist and food studies frameworks, this paper interprets The Mistress of Spices (1997) as a text that decolonises the kitchen, transforming culinary knowledge into a mode of resistance and reparation. In doing so, the novel positions food as both an affective and political medium through which marginalised voices reclaim agency and renegotiate belonging within Indian and global cultural imaginaries.